$f(x) = \frac{\int_{\alpha x}^{x} e^{-t} t^{b+1}\ dt}{x \int_{\alpha x}^{x} e^{-t} t^b\ dt}:\ ]\ 0,+\infty\ [\ \to \mathbb{R}$

where $\ 0<\alpha<1\ $ and $\ b>0$


First perform a change of variables in the integration using $t = sx$. This gives

$$ f(x) = \frac{\int_a^1 e^{-xs} s^{b+1}~ \mathrm{d}s}{\int_a^1 e^{-xs} s^{b} ~\mathrm{d}s} = - \frac{d}{dx} \ln \int_a^1 e^{-xs} s^b ~\mathrm{d}s $$

Define $$ g(x) = \int_a^1 e^{-xs} s^b ~\mathrm{d}s $$ you have $$ f'(x) \leq 0 \iff \ln g(x) \text{ is convex} \iff \ln g(\frac{\alpha + \beta}{2}) \leq \frac12 (\ln g(\alpha) + \ln g(\beta)) $$ this in turn $$ \iff g(\frac{\alpha+\beta}{2}) \leq \sqrt{g(\alpha)g(\beta)} $$

This final line holds by Cauchy-Schwarz applied to $e^{-\alpha s / 2} e^{-\beta s/2}$ integrating against the measure $s^b ~\mathrm{d}s$.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.